Le Corbusier : an atlas of modern landscapes - Cohen, Jean-Louis, 1949- (The Museum of Modern Art, 2013)
"This volume examines Le Corbusier's relationship with the topographies of five continents, in essays by thirty of the foremost scholars of his work and with contemporary photographs by Richard Pare. The Swiss-born, Paris-based architect is often remembered as having been aggressively indifferent to the sites of his buildings and plans, but this new generation of research, analysis, and interpretation asserts that even the most generic of his projects responded to specific geographies. His sketchbooks, letters, and publications confirm that he was deeply involved with both optical and bodily relationships to landscape over the course of his creative life, from his beginnings in Switzerland, as a disciple of the regional style sapin in his hometown of La Chaux-de-Fonds, to the creation of the new Indian city of Chandigarh; from touring Europe in his Avions Voisin automobile to mapping South America from the air; from inserting grand plans into existing urban layouts to setting a chapel atop an isolated hill in Ronchamp. Whether in an intimate suburban plot or against a dramatic horizon, Le Corbusier transformed territories into landscapes." -- Vydavatelská anotace